2022
DOI: 10.1177/0310057x211059191
|View full text |Cite
|
Sign up to set email alerts
|

The association between unanticipated prolonged post-anaesthesia care unit length of stay and early postoperative deterioration: A retrospective cohort study

Abstract: This study aimed to investigate whether there was an association between an unanticipated prolonged post-anaesthesia care unit (PACU) length of stay and early postoperative deterioration, as defined as the need for a rapid response team activation, within the first seven days of surgery. We conducted a single-centre retrospective cohort study of adult surgical patients, who stayed at least one night in hospital, and were not admitted to critical care immediately postoperatively, between 1 July 2017 and 30 June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Patients who involved such issues might experience longer PACU stays than those who did not, which is consistent with other studies. [ 8 , 15 , 16 ] Hypotension, hypoxia, tachycardia were the critical incidents. Kluger and Bullock also reported that the majority of recovery room incidents were cardiorespiratory related.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who involved such issues might experience longer PACU stays than those who did not, which is consistent with other studies. [ 8 , 15 , 16 ] Hypotension, hypoxia, tachycardia were the critical incidents. Kluger and Bullock also reported that the majority of recovery room incidents were cardiorespiratory related.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory depression (Laporta et al, 2020), neurological events, including emergence agitation or delirium (Jin et al, 2020), post-operative nausea and vomiting (Schlesinger et al, 2023), abnormal temperature (Kim et al, 2019) and even cardiac arrest (Kaiser et al, 2020) might occur during this critical period. Unexpected adverse events during the anaesthesia recovery period might lead to early post-operative deterioration of the patient's health, possibly resulting in prolonged hospitalization or even death (Fletcher et al, 2022). Therefore, it is critically important for nurses to closely monitor patients who are recovering from anaesthesia.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“… 1 Delay in transferring the patient out of the PACU can result in a range of adverse consequences for the patient, such as increased postoperative complications, prolonged recovery time, and inefficient utilization of healthcare resources. 2 Given the escalating number of patients undergoing surgical procedures, 3 the PACU has become an important link in the continuum of care, responsible for the postoperative monitoring and treatment of patients, thereby under tremendous pressure due to the high patient turnover. However, the use of standardized assessment tools for PACU discharge can improve PACU turnover rates, reduce complications, and ensure postoperative patient safety.…”
Section: Introductionmentioning
confidence: 99%